Social Protection in Fragile and Conflict-Affected Countries : Trends and Challenges - Ovadiya, Mirey (World Bank, Washington, DC, 2015)
This study examines the role of social protection programming, and programming design and implementation features, that are prominent in fragile and conflict-affected states. The main objective is to build on existing, available information from a sample of fragile and conflict-affected countries and develop operational guidance that addresses policy, design, and implementation issues and offers operational solutions for social protection programming and policy making in different fragile settings. The analysis showcases the universe of social protection objectives that are evident in these countries as well as the programming trends, types, coverage, and expenditure patterns. The paper also examines dimensions specific to fragile and conflict-affected settings in implementing social protection and labor programs, such as social cohesion, the role of community-driven development, and postwar benefits. Finally, the study highlights social protection and labor program delivery in seven different country contexts, and discusses the country-specific programming options chosen to achieve the objectives and overcome capacity and operational constraints.